Contemporary adaptive divergence of plant competitive traits in urban and rural populations and its implication for weed management. (6th September 2020) - Fukano, Yuya; Guo, Wei; Uchida, Kei; Tachiki, Yuuya
Abstract: Competition among neighbouring plants plays essential roles in growth, reproduction, population dynamics, and community assembly, but how competition drives local adaptation and the traits underlying the adaptation remain unclear. Here, we focused on populations of the aggressive weed Digitaria ciliaris from urban and rural habitats as low‐ and high‐competition environments for light resources and examined how competitive interaction drove contemporary adaptive divergence of competitive traits. To examine local adaptation to different competitive environments in D. ciliaris and the specific traits that have been selected for, we compared growth rate and competitive traits in plants from farmland and urban populations between high‐ and low‐competition treatments. Furthermore, we conducted a field tillage experiment with drone (unmanned aerial vehicle) monitoring to examine the possibility that trait evolution in farmland habitats might influence weed management practices in crop fields. Plants from farmland populations had higher growth rates than plants from urban populations in high‐competition treatments, and vice versa in low‐competition treatments. Among populations, those with larger height/width ratios (farmland populations) were more tolerant of above‐ground competition in high‐competition treatments, but among individuals, those with larger ratios had lower growth rates in low‐competition treatments. More plants from farmland populations, which had thicker stems (and larger height/width ratios), survived after experimental tillage than plants from urban habitats with thinner stems. Synthesis . Our study empirically demonstrated adaptive divergence in competitive traits in above‐ground competitors and its underlying traits. Moreover, contemporary adaptive divergence between urban and rural plant populations has practical implications for weed control. The urban–rural model system can thus contribute to both basic and applied research in plant evolutionary ecology. Further research is required to understand adaptive divergence in plants between urban and rural environments, and the traits underlying the adaptation, not only above‐ground but also below‐ground. Abstract : To understand how competition drives local adaptation and trait change, we focused on urban and rural habitats as low‐ and high‐competition environments. We showed that farmland of Digitaria ciliaris, had greater height/width ratios with thicker stems and higher growth rates than urban genotypes in high‐competition treatments, and vice versa in low‐competition treatments. Furthermore, the farmland genotypes with thicker stems were more likely to survive following mechanical tillage.